2020
DOI: 10.3390/nu12061677
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Interactions between Folic Acid Supplementation and One Carbon Metabolism Gene Variants on Small-for-Gestational-Age Births in the Screening for Pregnancy Endpoints (SCOPE) Cohort Study

Abstract: Small-for-gestational-age (SGA) is associated with significant perinatal morbidity and mortality. Our aim was to investigate gene-nutrient interactions between maternal one-carbon single nucleotide polymorphisms (SNPs) and folic acid supplement (FAS) use, and their association with SGA. Nulliparous New Zealand women with singleton pregnancy were recruited as part of the Screening for Pregnancy Endpoints prospective cohort study. Data on FAS use was collected via face-to-face interview at 15 weeks’ gestation; p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Fetal growth and SGA or LGA results are influenced by different factors including maternal socio-demographic characteristics, health status, nutritional intake, environmental exposures, genetic background and gene-environment interactions [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fetal growth and SGA or LGA results are influenced by different factors including maternal socio-demographic characteristics, health status, nutritional intake, environmental exposures, genetic background and gene-environment interactions [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nurk’s study found no significant associations between MTHFR C677T and LBW in Norway [ 41 ]. Moreover, the Screening for Pregnancy Endpoints (SCOPE) prospective cohort study found no significant gene-nutrient interactions between maternal MTHFR C677T, MTHFR A1298C, and folic acid use, and their association with PTB and SGA [ 42 , 43 ]. The results of the three studies mentioned above were collaborative with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, new, emerging biomarkers have been discovered in the fields of genomics and proteomics, like exosomes, which are involved in the cellular cross-talks and related biological processes [16]. Nutrigenomics [17,18], epigenomics [19] and nutriepigenomics [20,21] investigate how dietary habits and nutrition, as well as environmental factors, and their complex, non-linear interactions can finely modulate the human genome and its expression, and impact on human diseases, including gynecological conditions. For instance, a study explored the relationship between folic acid supplementation and one carbon metabolism gene single nucleotide polymorphisms (SNPs) on small-for-gestationalage (SGA) births [17].…”
Section: Gynecology and Omics Datamentioning
confidence: 99%
“…Nutrigenomics [17,18], epigenomics [19] and nutriepigenomics [20,21] investigate how dietary habits and nutrition, as well as environmental factors, and their complex, non-linear interactions can finely modulate the human genome and its expression, and impact on human diseases, including gynecological conditions. For instance, a study explored the relationship between folic acid supplementation and one carbon metabolism gene single nucleotide polymorphisms (SNPs) on small-for-gestationalage (SGA) births [17]. Other studies assessed the association between pregnancy and childhood epigenetics [19,20].…”
Section: Gynecology and Omics Datamentioning
confidence: 99%